In-season strength maintenance training increases well-trained cyclists` performance - Ronnestad, B. R.; Hansen, E. A.; Raastad, T. (European Journal of Applied Physiology, 2010)
We investigated the effects of strength maintenance training on thigh muscle cross-sectional area (CSA), leg strength, determinants of cycling performance, and cycling performance. Well-trained cyclists completed either (1) usual endurance training supplemented with heavy strength training twice a week during a 12-week preparatory period followed by strength maintenance training once a week during the first 13 weeks of a competition period, or (2) usual endurance training during the whole intervention period. Following the preparatory period, E + S increased thigh muscle CSA and 1RM (p < 0.05), while no changes were observed in E. Both groups increased maximal oxygen consumption and mean power output in the 40-min all-out trial (p < 0.05). At 13 weeks into the competition period, E + S had preserved the increase in CSA and strength from the preparatory period. From the beginning of the preparatory period to 13 weeks into the competition period, E + S increased peak power output in the Wingate test, power output at 2 mmol l-1 [la-], maximal aerobic power output (W max), and mean power output in the 40-min all-out trial (p < 0.05). The relative improvements in the last two measurements were larger than in E (p < 0.05). For E, W max and power output at 2 mmol l-1 [la-] remained unchanged. In conclusion, in well-trained cyclists, strength maintenance training in a competition period preserved increases in thigh muscle CSA and leg strength attained in a preceding preparatory period and further improved cycling performance determinants and performance.